2022
DOI: 10.1177/13684302211042424
|View full text |Cite
|
Sign up to set email alerts
|

Resistance towards increasing gender diversity in masculine domains: The role of intergroup threat

Abstract: Efforts to increase diversity can often be met with resistance amongst high-status groups. Despite this, little is known about majority-group responses towards increasing gender diversity, and the psychological mechanisms underlying them. Across five studies, we extended intergroup threat theory to advance understanding of resistance towards gender diversity amongst men in masculine domains (Studies 1–3 and 5) and amongst women in feminine domains (Study 4). Experimental evidence from male STEM students (Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The Special Issue also highlights potential mediators of demographic or power shift effects, providing insights into the mechanisms (or the "why" questions). Understandably, most researchers pursued the notion of threat in its many forms, including status threat, realistic (i.e., tangible) threat (including perceived discrimination against the dominant group), symbolic threat (i.e., nontangible), or moral threat (e.g., Brown, Rucker and Richeson 2022;Domen, Scheepers, Derks and van Veelen 2022;Dover, 2022;Jones et al, 2022;Okuyan & Vollhardt, 2022;Reyna et al, 2022;Rivera-Rodriguez, Larsen and Dasgupta 2022). Most of these endeavors generally found that threats play a significant role in predicting a range of outcomes relevant to solidifying the status quo.…”
Section: Processes Underlying Shift Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Special Issue also highlights potential mediators of demographic or power shift effects, providing insights into the mechanisms (or the "why" questions). Understandably, most researchers pursued the notion of threat in its many forms, including status threat, realistic (i.e., tangible) threat (including perceived discrimination against the dominant group), symbolic threat (i.e., nontangible), or moral threat (e.g., Brown, Rucker and Richeson 2022;Domen, Scheepers, Derks and van Veelen 2022;Dover, 2022;Jones et al, 2022;Okuyan & Vollhardt, 2022;Reyna et al, 2022;Rivera-Rodriguez, Larsen and Dasgupta 2022). Most of these endeavors generally found that threats play a significant role in predicting a range of outcomes relevant to solidifying the status quo.…”
Section: Processes Underlying Shift Reactionsmentioning
confidence: 99%
“…This impressive range of methods evidenced in the Special Issue has expanded the boundaries of earlier racial shift paradigms to comprehensively explore reactions to changing demographics and privilege lost concerns. Our enthusiasm is bolstered by the direct efforts to experimentally reduce negative outcomes from demographic shifts (e.g., Jones et al, 2022) and by efforts to explore effects across different nations (see Stefaniak & Wohl, 2022). There remain, of course, challenges for the field, beyond simply the rather salient need to expand beyond the heavy US focus in this line of inquiry.…”
Section: Challenges and Opportunities For Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reasons might be internal to the company, such as its cultural norms and policies that govern how the organization operates and individuals within it act, think, and feel (Ehrhart et al, 2013; Ostroff et al, 2013). Depending on that internal culture, there may be unanticipated consequences such as pushback and other negative reactions (e.g., Jones et al, 2022) that could give rise to elevated animosity and discrimination against individuals already there (Leslie, 2019). Thus, raising the organization's level of diversity requires attention to how and why individuals both enter and leave the organization.…”
Section: Motivating Examplementioning
confidence: 99%
“…Thus, raising the organization's level of diversity requires attention to how and why individuals both enter and leave the organization. Recognizing this, Waldman and Sparr (2022) recently recognized the need for focusing on both diversity and unity to meet organizational and individual needs. Poor environments can simultaneously cause more individuals to leave the organization at the same time as those being brought in, canceling out potential gains or even outpacing them.…”
Section: Motivating Examplementioning
confidence: 99%